The physiological and perceptual responses of stand-up paddle board exercise in a laboratory- and field-setting - Willmott, A. G. B.; Sayers, B.; Brickley, G. (European Journal of Sport Science, 2020)
This study quantified the physiological and perceptual responses of stand-up paddle boarding (SUP) during a range of stroke rates in a laboratory- and field-setting. Ten participants (eight male, two female; mean ± standard deviation [SD] age: 23 ± 3 years; body mass: 70.5 ± 9.1 kg; height: 170 ± 9 cm; body mass index [BMI]: 24.3 ± 1.5 kg.m2) completed a SUP VO2peak trial, and two SUP trials in both a laboratory- and field-setting (5-min at 10, 20 and 30 strokes.min-1 per stage). Energy expenditure (EE), metabolic equivalents (METs), heart rate (HR) and rating of perceived exertion (RPE) were recorded throughout. In the laboratory-setting, mean ± SD EE and METs increased (P < 0.001) linearly when SUP at 10 (3.3 ± 1.0 kcal.min-1, 2.7 ± 0.5), 20 (5.5 ± 0.9 kcal.min-1, 4.4 ± 0.7) and 30 strokes.min-1 (7.6 ± 1.6 kcal.min-1, 6.1 ± 1.2), respectively. During these efforts, mean ± SD percentage of maximal HR were 56 ± 5%, 69 ± 6% and 84 ± 8%, respectively. In the field-setting, mean ± SD EE and METs also increased (P < 0.001) linearly when SUP at 10 (3.6 ± 0.9 kcal.min-1, 2.7 ± 0.9), 20 (4.3 ± 1.8 kcal.min-1, 3.5 ± 1.0) and 30 strokes.min-1 (6.3 ± 2.1 kcal.min-1, 4.6 ± 1.4). During the three conditions mean ± SD percentage of maximal HR were 58 ± 8%, 65 ± 7% and 73 ± 9%. SUP at =20 strokes.min-1 in the laboratory- and field-setting meet the criteria for moderate-intensity exercise (3.0-5.9 METs). These findings may now be included in the latest Compendium of Physical Activities guidelines and offer potential to improve cardiorespiratory fitness if SUP is undertaken regularly by young, healthy adults.